Vpliv kinematike perila v bobnu sušilnih strojev na učinkovitost procesa sušenja - Gatarić, Pero (visokošolska dela, 2021)
This work investigates the influence of drum inlet air parameters on a drying process in an open-cycle tumble dryer. Regression models were developed to determine the specific drying time, moisture evaporation rate and area-mass transfer coefficient. A higher volume flow rate and temperature and a lower relative humidity of the drying air increase the moisture evaporation rate, which decreases the specific drying time. A closed-cycle heat pump dryer was evaluated for energy consumption and drying time as a function of fan speed, drum speed, load mass, and refrigerant mass. An increase in drum speed, load mass and refrigerant mass has a positive effect on specific energy consumption and specific drying time. Furthermore, clothes kinematics and its effect on the heat pump dryer performance were examined in relation to the load mass, drum speed and drying stage, defined by a relative condensate mass. Clothes kinematics in the drum was recorded using a high-speed camera and evaluated by visualization method. Homogenous clothes distribution and reduction of tangling or local accumulation of clothes increase the contact area between the clothes and the drying air, which improves the moisture evaporation rate, drying efficiency and drying quality.
Keywords: clothes kinematics; convective textile drying; čas sušenja; Disertacije; dissertations; drying time; enakomernost sušenja; energijska učinkovitost; energy efficiency; evenness of drying; heat and mass transfer; heat pump tumble dryers; kinematika perila; konvektivno sušenje perila; prenos toplote in snovi; regresijska analiza; regression analysis; Sušilni stroji; sušilni stroji s toplotno črpalko; visualization; vizualizacija